Жоғары оқу орнында инновациялық технологияларды арнайы курста жүзеге асырудың тиімділігі - Қонақбаева, Т. Е. (My University, 2016)
Relevance: Entering some innovative technologies in a process of systematic and concrete teaching of personality in social-economical conditions in accordance with requirements of society. Goal: Analysing the contact of notion innovative technoiogy its necessary to show the efficiency of the usage IT on the special course in higher educational establishment. Method: Smart-board, electronic library, methodic and technology of special computer programmes. Result: The usage of innovative technologies is the base in gualitative differentiation of teaching process, in entering new projects and in a process of self-research of every student in building the methodical system by a teacher. Conclusions: In preparation of future pedagogue teaching staff improves his competences and skills its necesserary duply to master and realize methodical means and approaches as a result of the pedagogical experience.
Keywords: Pedagogical technology; innovation; future teacher; interactive methods